¿La autoestima y el género explican la depresión/ansiedad en los adolescentes? - Pereira da Silva, Brenda Fernanda (2022)
Depression and anxiety are common in adolescents, and poor mental health in this group leads to harm in adulthood. This study investigates to what extent gender, age, body image dissatisfaction, and self-esteem were related to depressive and anxiety symptoms in adolescents. The sample consisted of 1,209 high school students of both sexes, aged 13-19 years (M = 15.8; SD = 1.23). The instruments were: sociodemographic questionnaire, Rosenberg Self-Esteem Scale (RSES), Stunkard Figure Scale and the Hospital Anxiety and Depression Scale (HADS). Multinomial logistic regression indicated that being female and having low or moderate self-esteem satisfactorily explained the anxiety symptoms. Reduced self-esteem was the best explanation for depressive symptoms, and finally, reduced rates of self-esteem satisfactorily explained symptoms for both disorders.